ISLAMIC WEALTH MANAGEMENT IN MOSQUE FINANCIAL MANAGEMENT (CASE STUDY OF KAUMAN GREAT MOSQUE, YOGYAKARTA) - Rizqi Anfanni Fahmi; Ahmad Maslahatul Furqon; Hishamuddin Ismail (IAIN Manado, 2023)
A mosque is a sacred site of worship for Muslims. The mosque typically solicits contributions from the congregation to fund its activities. To be accountable for the congregations, therefore, the administrators of the mosques should practice sound financial administration. This study seeks to analyze Masjid Gedhe Kauman (Great Mosque Kauman), one of the oldest mosques in Yogyakarta, Indonesia, based on Islamic wealth management. It also has a wealth of historical significance due to Java's lengthy history of Islamization. It was situated around Kraton Palace, one of the ancient Javanese giant kingdoms. Islamic wealth management encompasses wealth creation, wealth accumulation, wealth protection, wealth purification, and wealth distribution. The data was collected by interviewing the mosque administrator, documenting the financial report, and observing the activities. The results indicate that the Kauman Great Mosque in Yogyakarta has not yet fully implemented the Islamic Wealth Management concept into its financial management. Wealth accumulation and wealth purification have not yet received sufficient attention from mosque administrators. Authority status, government policies, and ownership are the primary obstacles to developing mosque financial management. The majority of the funds for the Kauman Great Mosque in Yogyakarta originate from infa (alms). The fund prioritizes initiatives associated with mosques. The discovery also reveals a lack of transparency in financial management, as the congregation does not have access to the financial report despite the inactive fund exceeding one billion rupiah. ‎ The study proposes the implementation of contemporary financial management strategies in order to bolster self-reliance, foster the productive utilization of mosque assets, and prioritize the safeguarding of wealth.